After work: en longitudinell studie i arbetsmiljöns långsiktiga inverkan på sambandet mellan socioekonomisk position och äldres ohälsa (Sociologisk Forskning, 2010)
After Work. The long-term effects of work environment on the association between adult socioeconomic position and ill health among the elderlyThe aim of this study is to analyse the long-term effects of work environment on the association between adult socioeconomic position (SEP) and six ill health outcomes among the elderly.Data was drawn from the longitudinal Level of Living and the SWEOLD-surveys. The individuals are followed from 1968 to 1992 and from 1981 to 2002 and 2004, combining baseline information regarding SEP and work environment during the period of occupational activity with the ill health outcomes from the follow-up studies.Strongest effects where revealed when controlling for the physical work environment on the association between both measures of SEP and two of the ill health outcomes: musculoskeleta lpain and physical performance. The psychological work environment, however, explained very small parts of the associations. The results, even controlled for SEP, exposed strong direct relations between ill health and psychological work environment and rather strong relations to physical work environment.As socioeconomic position indicates a particular structural position within society it may determine the likelihood of health damaging exposures during the period of occupational activity. This study shows that the effect of work environment significantly affects ill health among the elderly. Hence, the results indicate the importance of taking measures in improving work environment during the labour-market participation period, especially since policy-makers attempt to convince workers to stay longer in the workforce.